Reactive bonding film for bonding carbon foam through metal extrusion. (21st March 2017) - Chertok, M.; Fu, M.; Irving, M.; Neher, C.; Tripathi, M.; Wang, R.; Zheng, G.
Abstract: Future tracking detectors, such as those under development for the High Luminosity LHC, will require mechanical structures employing novel materials to reduce mass while providing excellent strength, thermal conductivity, and radiation tolerance. Adhesion methods for such materials are under study at present. This paper demonstrates the use of reactive bonding film as an adhesion method for bonding carbon foam.